Parallel evolution, atavism, and extensive introgression explain the radiation of Epimedium sect. Diphyllon (Berberidaceae) in southern East Asia - Zhang, Cheng; Meng, Ran; Meng, Ying; Guo, Bao-Lin; Liu, Quan-Ru; Nie, Ze-Long (Frontiers in Plant Science, 2023)
East Asia is the richest region of plant biodiversity in the northern temperate zone, and its radiation provide key insights for understanding rapid speciation, including evolutionary patterns and processes. However, it is challenging to investigate the recent evolutionary radiation among plants because of the lack of genetic divergence, phenotypic convergence, and interspecific gene flow. Epimedium sect. Diphyllon is a rarely studied plant lineage endemic to East Asia, especially highly diversified in its southern part. In this study, we report a robust phylogenomic analysis based on genotyping-by-sequencing data of this lineage. The results revealed a clear biogeographic pattern for Epimedium sect. Diphyllon with recognition into two major clades corresponding to the Sino-Himalayan and Sino-Japanese subkingdoms of East Asian Flora and rapid diversification of the extant species dated to the Pleistocene. Evolutionary radiation of Epimedium sect. Diphyllon is characterized by recent and predominant parallel evolution and atavism between the two subkingdom regions, with extensive reticulating hybridization within each region during the course of diversification in southern East Asia. A parallel-atavism-introgression hypothesis referred in explaining the radiation of plant diversity in southern East Asia, which represents a potential model for the rapid diversification of plants under global climate cooling in the late Tertiary. Our study advances our understanding of the evolutionary processes of plant radiation in East Asia as well as in other biodiversity hotspot regions.